Teaching English as A Foreign Language at Madrasah Ibtidaiyyah: Facts and Challenges - Nashruddin, Wakhid (Dinamika Ilmu, 2015)
The mastery of English as a tool of communication among nations, cultures, and people around the globe is an undeniable fact. This is just like an unstoppable virus spreading worldwide. It is rather difficult to emerge new languages to stop or even just to slow down the wide use of English. Islam world also needs to follow this by equipping its people with English as a communication tool. As Arabic is used for the communication inside Islam, English is needed to communicate Islam to other people around the earth both to Muslims or Non-Muslims. Teaching English has become an increasingly significant element in Islamic education. For this, the issue of teaching English at madrasah is an important concern for practitioners in the area of TEFL in Islamic institutions. This paper will explore the writerâs ten-year experience in teaching English at a madrasah ibtidaiyyah in Cirebon, West Java-Indonesia. The conditions that will be pictured are the culture, the students, the teaching and learning process, and the outcome of the current practices in madrasah ibtidaiyyah, mainly in the area of TEFL. Then, all these conditions will be contrasted to up to date research findings and theories so that the facts and the challenges can be clearly seen. This will also be seen from the perspective of current curriculum in Indonesia, namely curriculum 2013, which bears contradictions with the presence of it. In fact, the curriculum 2013 eliminates English as a subject learned at primary school level. What madrasah ibtidaiyyah will do in the next coming years can direct the expected outcome of the teaching of English at this level. Kinds of program that can be designed to empower the state of English mastery are an essential case to discuss. This all facts and challenges can provide insights so that people working in and with madrasah ibtidaiyyah understand and are ready to face the global communication era.